Effect of Internal Control, Accounting Information System, and Employee Performance on Financial Reporting Quality at Public Works Department of Muara Enim Regency - Eltha Hasaelvana; Andini Utari Putri; R. Moh. Rum Hendarmin (Golden Ratio of Auditing Research, 2026)
This study aims to analyze the influence of Internal Control, Accounting Information Systems, and Employee Performance on the Quality of Financial Reports at the Public Works and Spatial Planning Agency of Muara Enim Regency. The approach used is a quantitative method with data collection techniques through questionnaires distributed to employees directly involved in the process of preparing financial reports and internal auditors or inspectorates. Data analysis was conducted using multiple linear regression to test the influence of each variable partially and simultaneously. The results of the study indicate that partially, Internal Control, Accounting Information Systems, and Employee Performance have a positive and significant effect on the Quality of Financial Reports. Simultaneously, these three variables also have a significant effect on the Quality of Financial Reports. These findings indicate that the implementation of effective internal controls, optimal use of accounting information systems, and good employee performance can improve the quality of government agency financial reports. This study provides practical implications for government agencies to continue to strengthen internal control systems, maximize the use of accounting information technology, and increase human resource capacity to realize quality financial reports.